Bacterial biofilm colonization and succession in tropical marine waters are similar across different types of stone materials used in seawall construction - Summers, Stephen; Pek, Y. Shona; Vinod, Deepthi P.; McDougald, Diane; Todd, Peter A.; Birch, William R.; Rice, Scott A. (Frontiers in Microbiology, 2022)
Seawalls are important in protecting coastlines from currents, erosion, sea-level rise, and flooding. They are, however, associated with reduced biodiversity, due to their steep orientation, lack of microhabitats, and the materials used in their construction. Hence, there is considerable interest in modifying seawalls to enhance the settlement and diversity of marine organisms, as microbial biofilms play a critical role facilitating algal and invertebrate colonisation. We assessed how different stone materials, ranging from aluminosilicates to limestone and concrete, affect biofilm formation. Metagenomic assessment of marine microbial communities indicated no significant impact of material on microbial diversity, irrespective of the diverse surface chemistry and topography. Based on KEGG pathway analysis, surface properties appeared to influence the community composition and function, during the initial stages of biofilm development, but this effect disappeared by Day 31. We conclude that marine biofilms converged over time to a generic marine biofilm, rather than the underlying stone substrata type playing a significant role in driving community composition.